[PP.27.24] DIAGNOSTIC ACCURACY AND DIAGNOSTIC GAIN OF CRITERIA TO INTERPRET UNILATERALLY SELECTIVE ADRENAL VEIN SAMPLING (AVS) RESULTS. (September 2017) - Barigou, M.; Amar, L.; Baron, S.; Cornu, E.; Lethielleux, G.; Grataloup, C.; Pagny, J.-.Y.; Carrere, T.; Laffy, P.-.Y.; Madjalian, A.-.M.; Zinzindohoue, F.; Azizi, M.; et al.
Abstract : Objective: 10–20% of AVS performed in Excellence centers for primary aldosteronism (PA) are not bilaterally selective. The ratio of cortisol-corrected aldosterone concentration between adrenal vein and inferior vena cava (unilateral ratio, UR) has been proposed to interpret unilaterally selective AVS [1]:UR<0.5could suggest unilateral PA on the opposite side; UR >5.5 could suggest unilateral PA on the same side, and UR 0.5–5.5 would be inconclusive. Design and method: This retrospective study evaluates the diagnostic value of the UR on AVS data collected over10 years in a referral centre. French AVS-consensus criteria (selectivity index >2, lateralisation ratio >4) were used for AVS interpretation. We first assessed the numbers of cases with left and right UR both <0.5 or both >5.5, because in these cases the interpretation of unilaterally selective AVS will depend only on the side of successful adrenal vein cannulation, not on the side of the disease. We then assessed the sensitivity, specificity and PPV of these criteria for the diagnosis of unilateral PA. Cases with left and right UR both <0.5 or both >5.5 were counted as false positives for these calculations. We finally assessed the diagnostic impact of using the unilateral criteria in case of unilaterally selective AVS. Results: -537AVS were performed from 2001–2010, 64(12%) were not bilaterally selective using the reference criteria (28unilaterally selective and 36 bilaterally non-selective), 287 (53%) were diagnostic of bilateral PA, 99 (18%) of left PA and 87 (16%) of right PA [Table 1]. -Among 473 bilaterally selective AVS, 7 (1.5%) had left and right UR both <0.5 and 32 (7%) had left and right UR both >5.5 [Table 2]. -Sensitivity of UR <0.5 to detect unilateral PA was 55%, specificity 91%, PPV79%. -Sensitivity of UR >5.5 was 51%, specificity71%, PPV53% [Table3]. -Using these criteria to interpret 28 unilaterally selective AVS led to diagnose 2right PA but 0left PA with a contralateral UR <0.5, 10 right PA and 6left PA with an ipsilateral UR >5.5, the remaining 10 cases staying inconclusive. However, among the 16 unilateral PA diagnosed with an ipsilateral UR >5.5, we must expect 8 false positives. Figure. No caption available. Conclusions: -Using an UR>5.5to diagnose ipsilateral PA in unilaterally selective AVS is potentially dangerous. Almost half of these patients are false positive (sometimes contralateral PA). -Using a UR <0.5to diagnose contralateral PA in unilaterally selective AVS is less prone to error but with limited diagnostic yield. -We should assess the combining of these criteria withf adrenal imaging to improve their diagnostic performances.